Equine Field Anesthesia - Aguiar, Antonio José de Araujo [UNESP] (Wiley, 2017)
The administration of intravenous anesthetics to horse requires much attention and care. This chapter highlights concerns and facts to consider concerning preparation of the patient to be anesthetized under field conditions. In adult horses, recumbency is accompanied by significant alterations in cardiovascular and respiratory systems. Thus, general anesthesia of a horse under field conditions should be performed in clinically healthy patients. It is vital to anticipate and react to the horse’ movements immediately after the administration of the induction agents, assisting it at the critical moment of recumbency. The choice of protocol depends on the clinical state of the patient, the expected time to perform the surgical procedure, the premedication previously administered, and personal experience/preference with induction technique. Management of the time of anesthesia and surgical/diagnostic procedures is crucial in determining the total amount of drugs administered, which then have to be biotransformed and eliminated from the horse’ body.
Keywords: anesthesia recovery; equine field anesthesia; horse’ movements; premedication; recumbency